ECO-FRIENDLY CARS’ PURCHASES: THE ROLE OF CONSUMER ENVIRONMENTAL CONCERN, MONETARY POLICY, AND VALUE PERCEPTIONS - Elisa, Santa; Tjokrosaputro, Miharni (Graduate Program of Universitas Tarumanagara, 2024)
In the automotive market environment of Indonesia, a more in-depth insight into the factors that influence the purchase intention of eco-friendly cars is essential. Environmentally friendly cars are increasingly gaining attention amidst global environmental and climate change concerns. The research method used was a survey with data collection through a questionnaire distributed to 300 respondents by using purposive sampling. The measurement scale in this study used a 7-point Likert scale. Most respondents are female, comprising 56 percent, compared to 44 percent of male respondents. Most respondents with entrepreneurial backgrounds and bachelor’s degrees fall within the productive age range of 35 to 45 years. Additionally, a significant portion of the respondents earns an annual income ranging from 5 to 10 million Indonesian Rupiah. The analysis of the variance-based SEM method, PLS-SEM, shows that consumer environmental concern, monetary incentive policy measures, and perceived value significantly contribute to consumer purchase intentions. This research aims to positively contribute to advancing the eco-friendly car industry, bolster sustainable government policies, and shape consumer perceptions favorably towards greener transportation solutions. The study contributes valuable insights to this field’s existing literature and research. The empirical basis and findings derived from this research can serve as a reference for future studies on eco-friendly cars, providing a foundation for further exploration and understanding sustainable mobility choices